What Were the Sadducees Reading? An Enquiry into the Literary Background of Mark 12:18-23 - Bolt, Peter G. (Tyndale bulletin, 1994)
Where did the Sadducees’ case study (Mk. 12:20-23) originate? After dismissing 2 Maccabees 7, this article suggests that the Book of Tobit most probably provides the Sadducees with their story. Both they and Tobit talk of the death of 7 husbands and Levirate marriage in the context of an interest in resurrection. The article ends by suggesting that this allusion to Tobit may bring further nuances to the reading of the Gospel of Mark.